(untitled) (Boston, 2006)
This lab manual provides a host of hands-on exercises that are the perfect supplement to your computer security textbook. Over 40 lab projects build from basic networking skills to identification of vulnerabilities, hardening of computer systems, and detection and incident response. This book reinforces Security+ certification objectives and prepares students to work in the real world by applying networking concepts to solve real business problems.
Keywords: Computer security,Data protection,Bảo mật máy tính,Bảo mật dữ liệu; Management,Handbooks, manuals, etc.,Handbooks, manuals, etc.,Quản lý